Exploring the Association Among Just in Time, Total Quality and Supply Chain Management Influence on Firm Performance: Evidence from Indonesia - Agustinus Nugroho; Budiman Christiananta; Fenika Wulani; Ikbar Pratama (International Journal of Supply Chain Management, 2020)
Abstract- Various methods are under current debate among academia to strengthen the efficiency of the operations. In general, three of them have gained significant recognition in the literature i.e. just in time, supply chain management and quality control. This research investigates the associations among supply chain management (SCM), just in time and quality management and also their impact on organizational performance. Findings suggest that at all strategic and functional levels, there are associations among just in time (JIT), TQM, and supply chain management and are perceived as a significant role in the operational course of actions of the firms. Statistics also demonstrate that dedication to quality and supply chain management dimensions have the highest impact on performance.